Interplay of piezoresponse and magnetic behavior in Bi0.9A0.1FeO2.95 (A = Ba, Ca) and Bi0.9Ba0.05Ca0.05FeO2.95 co-doped ceramics. Issue 4 (18th January 2022) - Mangamma, G.; Das, B. K.; Ramachandran, B.; Ramachandra Rao, M. S.; Sairam, T. N.
Abstract : In the pristine as well as the doped BiFeO3 samples, ferroelectric domains show switching behavior. The regions marked by yellow color loops show either 71° or 109°-domains, whereas those marked by white loops are 180°-domains. Abstract : Extensive piezoresponse force microscopy (PFM) and magnetic force microscopy (MFM) measurements in conjunction with piezoresponse spectroscopy have been carried out on pellets of Bi0.9 A0.1 FeO2.95 (A = Ba, Ca) and Bi0 .9 Ba0 .05 Ca0 .05 FeO2.95 co-doped ceramic samples in order to characterize their ferroelectric and magnetic nature and correlate the findings with our recent far-infrared spectroscopic studies on these samples. We are able to clearly discern the switching behavior of the 71° and 109° ferroelectric domains as distinct from that of the 180° domains in both pristine and Ba-doped bismuth ferrite samples. While substitution of Ba at the Bi site in bismuth ferrite does not affect the ferroelectric and magnetic properties to a great extent, Ca-doped samples show a decrease in their d 33 values with a concomitant increase in their magnetic behavior. These results are in agreement with the findings from our far-infrared studies.